INOVASI MEDIA FILTER BERBAHAN DASAR PASIR KWARSA DAN KARBON ORGANIK KULIT BUAH AREN UNTUK PROSES PENGOLAHAN AIR BERSIH DI PT. AIR MINUM INTAN BANJAR (PERSERODA) - Utomo, Budi; Heryani, Hesty; Suyanto, Suyanto; Sofarini, Dini (EnviroScienteae, 2023)
Population growth requires the provision of clean water that meets the standards. As a provider of clean water. PT.Air Minum Intan Banjar (Perseroda) needs to continue to innovate in the water treatment process. One of them is in the filtration process. The purposes of the research were to analyze the thickness variations of the filter media from Quartz sand and palm sugar peel in the filtration process and to analyze the water resulted from the filtration process through laboratory tests. The variations of filter media thickness, namely: 30 cm, 40 cm, 50 cm, 60 cm and 1 control. The treatments were conducted with 20 repetitions which were taken randomly using the Complete Randomized Design (RAL) method. The samples from the treatment were analyzed in the laboratory to be compared to the parameters of Clean Water Standard from Permenkes RI No. 492 year 2010, namely: Turbidity, Color, TDS, pH, Fe, Mn, Nitrate, Nitrite, Sulfate, and E. Coli. The results of statistical data analysis showed that there was a significant change in the reduction of several pollutant loads through the filtration process using filter media from Quartz sand and organic carbon of sugar palm peels. The reduction of the pollutant loads especially in the thickness variation of 60 cm. The reduction of the pollutant loads is on several parameter, namely: Turbidity, Color, TDS, Fe, Mn, Nitrate, and Nitrite. However, the variation treatment of the thickness of the quartz sand filter media and the organic carbon of sugar palm peels at all thicknesses did not have significant change to the levels of pH, Sulfate and the amount of E. Coli between raw water and treated water in the filtration process.